Faktor-Faktor yang mempengaruhi persepsi ibu terhadap kanak-kanak dengan kecacatan klef - Mohd Rohaizat Hassan,; Mohd Hafiz Yahya,; Normala Basiron,; Zairizam Zakaria,; Mohd Rizam Abdul Rahman,; Hazlina Mohd Miskam,; Sazman Wahab,; Norfazilah Ahmad,; Azmawati Mohammed Nawi,; Nazarudin Safian, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Introduction A study was conducted to determine the level of mothers' perception on children with cleft deformity and its associated factors Methods This was a cross sectional study involving 110 mothers with children attending the Plastic And Reconstructive Surgery Clinic. Data was gathered from a face to face interview based on a questionnaire that assesses the level of perception and its associated factors. The level of perception was evaluated from a scoring method and divided into four domains namely psychosocial, care management, treatment and education. Results The level of perception was high in all four domains ranged from 62% for treatment and 80% for education. Factors that were significantly associated with the level of perception were ethnicity, religion, type of cleft deformity and level of information. Conclusions Information regarding cleft deformity must be tailored toward mothers’ personal characteristics and type of cleft deformity to improve mothers' perception on this problem.